Cost analysis comparing guideline-oriented biopsychosocial management to usual care for low-back pain: a cluster-randomized trial in occupational health primary care - Maija Paukkunen; Jaro Karppinen; Birgitta Öberg; Leena Ala-Mursula; Eveliina Heikkala; Katja Ryynänen; Riikka Holopainen; Samuel Booth; Neill Booth; Allan Abbott (Scandinavian Journal of Work, Environment & Health)

(untitled)
OBJECTIVES: This study aimed to investigate the effect of a brief training intervention for occupational health services (OHS) professionals on multiprofessional resource utilization and the costs of biopsychosocial management of patients with low-back pain (LBP) compared to usual care among all participants and those in work disability-based risk groups. METHODS: OHS utilization and back-related sick leave data were collected from electronic patient records over one-year follow-up comparing 232 patients in the intervention arm and 80 control-arm patients, stratified for risk of work disability based on the Örebro Musculoskeletal Pain Screening Questionnaire. We estimated costs using linear mixed models by multiplying unit costs (in euros) by each type of OHS resource use (visits to physicians, physiotherapists, nurses, use of imaging) and the number of sick leaves. Estimated mean cost differences with confidence intervals (CI) were reported using bootstrapping to deal with skewed cost data. RESULTS: The median number of visits to physicians and physiotherapists in the intervention versus control arms was 1 [interquartile range (IQR) 0–3] and 2 (IQR 1–4) versus 2 (IQR 1–3) and 1 (IQR 0–2), respectively. The intervention arm accrued lower physician costs (€-43, 95% CI €-82– -3, P=0.034) and higher physiotherapist costs (€55, 95% CI €26–84, P<0.001) compared to the control arm. There was no statistically significant difference in average total costs between the arms (€-1908, 95% CI €-6734–2919). In the low- and medium-risk groups of work disability, physiotherapist costs were higher in the intervention than control arm, but no statistically significant differences were observed between the arms in the total resource utilization or sickness absence costs. CONCLUSIONS: Brief biopsychosocial training may support shifting OHS resources towards multiprofessional physiotherapist-driven care, instead of solely physician-driven care, for management of patients with LBP in differing risk groups of work disability with no substantial differences in total costs.